Real-Time personalized stress detection from physiological signals - Syazani, Muhammad; Khalifa, Othman Omran; Saeed, Rashid Abdelhaleem (2015)
This is the era of modern life. The era of email, text messages, Facebook and Twitter, careers Crisis news coming from everywhere at any time. We (human) are assaulted with facts, pseudo facts, jibber-jabber, and rumour all posing as information. We text while we’re walking across the street, catch up on email while standing in a queue. When people think they’re multitasking, they’re actually just switching from one task to another very rapidly. It has been found to increase the production of the stress that results overstimulate brains and cause mental fog or scrambled thinking. However, stress management should start far before the stress start causing illnesses. In this paper, a real-time personalized stress detection system from physiological signals is introduced. It is based on Pulse rate and temperature. That could record a person’s stress levels.